Mikami-Weinstein Type Theorem for Cosymplectic Groupoid Actions - Yonehara, Shuhei (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
The Mikami-Weinstein theorem is a generalization of the classical Marsden-Weinstein-Meyer symplectic reduction theorem to the case of symplectic groupoid actions. In this paper, we introduce the notion of a cosymplectic groupoid action on a cosymplectic manifold and prove a theorem that is a natural analogue of the Mikami-Weinstein theorem.